Reduced Brainstem Volume After Mild Traumatic Brain Injury. (May 2021) - Kim, Eunkyung; Seo, Han Gil; Lee, Hyun Haeng; Lee, Seung Hak; Choi, Seung Hong; Yoo, Roh-Eul; Cho, Won-Sang; Yun, Seo Jung; Kang, Min-Gu; Oh, Byung-Mo
Abstract : Objective: The aims of this study were to investigate changes in regional brain volume after concussion (mild traumatic brain injury) and to examine the relationship between change in brain volume and cognitive deficits. Design: Twenty-eight patients with mild traumatic brain injury and 27 age-matched controls were included in this study. Magnetic resonance imaging (3 T) data were obtained from the participants. Structural brain volume changes were examined using tensor-based morphometry, which identifies regional structural differences in the whole brain, including cerebrospinal fluid, gray matter, and white matter. Volume contraction and expansion were compared between groups using a two-sample t test. The association between time post-injury or neurocognitive function and volumetric changes was examined using regression analysis. Results: Individuals with mild traumatic brain injury exhibited volume reduction in the brainstem, including the pontine reticular formation. Regional cerebral volume changes were not associated with time post-injury but were significantly associated with neurocognitive function, especially with executive card sorting test, forward digit span test, and performance on verbal learning test. The greater regional cerebral volume was associated with better cognitive performance after mild traumatic brain injury. Conclusion: Decreased brainstem volume may indicate its vulnerability to traumatic injury, and cerebral volume in specific regions was positively associated with patients' cognitive function after injury. Abstract : Supplemental digital content is available in the text.